HOW THE CORRUPTION ERADICATION COMMISSION (KPK) PROMOTES ANTI-CORRUPTION PRACTICES IN INDONESIA - I Gede Sujana; I Gusti Ngurah Santika; I Putu Windu Mertha Sujana; I Nengah Suastika; I Wayan Wiryawan; Ni Nyoman Sri Mastini (CV. Tirta Pustaka Press, 2026)
Corruption remains a persistent challenge to governance, public trust, and socio-economic development in Indonesia. This study examines the role of the Corruption Eradication Commission (Komisi Pemberantasan Korupsi, KPK) in fostering an anti-corruption culture, focusing on its dual mandate of enforcement and prevention. Using a qualitative case study approach, data were collected through document analysis of KPK reports, academic literature, and media sources published between 2015 and 2023, with source triangulation applied to enhance validity. Findings indicate that the KPK’s high-profile prosecutions have contributed to a deterrent effect, as reflected in increased public awareness and shifts in perceptions of accountability and integrity. The analysis also shows that preventive initiatives, such as public awareness campaigns, integrity education in schools, and community engagement programs, are associated with increased public understanding of anti-corruption values. However, the effectiveness of these initiatives is constrained by several factors. Institutionally, legal restrictions following the 2019 revision of the KPK Law have limited operational independence. Politically and socially, persistent patronage networks and public tolerance for petty corruption continue to undermine anti-corruption efforts. The study concludes that a synergistic approach integrating enforcement, education, and public participation is essential, and highlights the KPK as a case demonstrating how anti-corruption agencies can function as both legal enforcers and agents of cultural change in developing democracies. The KPK exemplifies how an independent anti-corruption agency can act as both a legal enforcer and a cultural catalyst, offering a model for institutionalizing ethical governance in complex political contexts.